The influence of recruitment, training and compensation on employee performance at PT. Tirtayasa lestari surabaya - Abdul Kadir; Melania, Melania; Fredy Jayen; Rifqi Amrulloh (Jurnal Ekonomi, 2024)
PT. Tirtayasa Lestari Surabaya is one of the companies engaged in bathroom equipment (sanitary) which is developing in Surabaya. PT.Tirtayasa Lestari focuses on creating a boutique experience where every object is always displayed with context in mind so that anyone who comes is inspired to design a space that is both fun and healthy. The purpose of this research is to prove and analyze the effect of recruitment, training and compensation on employee performance at PT. Tirtayasa Lestari Surabaya. The analytical tools used in this research are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, correlation test, coefficient of determination test, F test and t test. The sampling method is using the population for employees at PT. Tirtayasa Lestari from the general division with a total of 45 respondents. The results showed that recruitment had a significant effect on employee performance at PT. Tirtayasa Lestari Surabaya, training had a significant effect on employee performance at PT. Tirtayasa Lestari Surabaya, compensation had a significant effect on employee performance. at PT. Tirtayasa Lestari Surabaya. Based on the results of the analysis, it shows that recruitment, work motivation, training and compensation simultaneously affect employee performance that is equal to 69.7 and the remaining 30.3% is influenced by other variables outside the variables used in this study.